2020
DOI: 10.1002/ctm2.111
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced CT radiomics for preoperative evaluation of microvascular invasion in hepatocellular carcinoma: A two‐center study

Abstract: Background The present study constructed and validated the use of contrast‐enhanced computed tomography (CT)‐based radiomics to preoperatively predict microvascular invasion (MVI) status (positive vs negative) and risk (low vs high) in patients with hepatocellular carcinoma (HCC). Methods We enrolled 637 patients from two independent institutions. Patients from Institution I were randomly divided into a training cohort of 451 patients and a test cohort of 111 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 38 publications
2
56
1
Order By: Relevance
“…Radiomics have exhibited great potential in predictive/discriminative models by integrating diseaserelated imaging features with clinical, pathological, and genetic data (22)(23)(24). Progress has been made in applying CT or MRI based radiomics for investigating MVI in HCC (25)(26)(27)(28). However, most studies only included a single phase of dynamic contrastenhanced (DCE)-CT or MRI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiomics have exhibited great potential in predictive/discriminative models by integrating diseaserelated imaging features with clinical, pathological, and genetic data (22)(23)(24). Progress has been made in applying CT or MRI based radiomics for investigating MVI in HCC (25)(26)(27)(28). However, most studies only included a single phase of dynamic contrastenhanced (DCE)-CT or MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, key image information beyond the tumor core might be lost since MVI often occurs in regions neighboring the tumor/non-tumor interface ( 6 , 29 ). Image texture from the peripheral liver parenchyma, such as a settled 5mm or 10mm distance from the tumor edge, have shown encouraging predictive ability in MVI ( 26 , 28 , 30 ). To our knowledge, no study has comprehensively reported on MVI predictive performances using different combinations of DCE-CT/MRI phase(s) with varying distances from the tumor margin.…”
Section: Introductionmentioning
confidence: 99%
“…2019), while those with solitary tumor displayed MVI are not easy to be identi ed. For patients with multiple tumors, previous studies only assessed the largest tumor to predict MVI status (Xu et al 2019;Zhang et al 2020b) but it is not accurate to identify which lesion exists MVI. The other point is that multicarcinogenesis may not be controlled by extended liver resection due to the limited liver volume.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial temporalization of clinical images has been developed and evidenced as a critical approach in clinical and translational practices, e.g., radiomics which was used to detect the alternations in the microenvironmental circulation and vascularization in solid tumors and to predict the prognosis of patients. 6,7 In addition, clinical images represent multi-dimensional events of organs and/or tumors and can be dynamically monitored. Rizk evidenced that the dynamic three-dimensional volume, velocity, and vascularization of the MRI-based heart could demonstrate the quantity and quality of hemodynamics in physiological and pathophysiological conditions through adequate spatiotemporal resolution.…”
Section: Improving Uses Of Spatiotemporal Clinical Imagesmentioning
confidence: 99%